Student Behaviour Relationship of the Profession to Use of Amoxicillin Antibiotic on Posterior Tooth Extraction at RSIGM YW-UMI Makassar in 2019 - Lestari, Nurasisa; Ilmianti, Ilmianti; Rasdayanti, Nur (International Journal of Halal System and Sustainability https://jurnal.narotama.ac.id/https://www.spb.gba.gov.ar/campus/https://conference.trunojoyo.ac.id/https://ojs.ucp.edu.ar/https://libros.cimsur.unam.mx/https://ojs.stikesmucis.ac.id/http://medi, 2023)
Bacterial resistance to antibiotics is a global threat to health. Health workers Knowledge, especially professional students who will become a dentist, is needed to prevent antibiotics abuse. Amoxicillin, including antibiotics, plays an important role in oral surgery. Antibiotics are compulsory for patients undergoing procedures action, especially for tooth extraction. The knowledge and attitudes of professional students are the components of behaviours interconnected in determining the use of antibiotics. To discover the behavioural relationship of professional students interviewed for aspects in knowledge, attitudes and actions on the use of amoxicillin antibiotics on the posterior tooth extraction. The research was analytic observation using the cross-sectional method. The research instrument used questionnaires related to knowledge, attitudes and actions of professional students on the use of amoxicillin antibiotics on the posterior tooth extraction. Statistical test results of Chi-Square acquired knowledge (? ?????= 0.04 greater than α = 0.05, attitude (? ?????=0.04 greater than α = 0.05) and action-based behavior (? ?????= 0.036 greater than α = 0.05). It found a significant relation between the professional student behaviour interviewed for the knowledge, attitude, and action on antibiotic use.